HUBUNGAN OBESITAS DENGAN KEJADIAN PREEKLAMSIA PADA IBU HAMIL - Sari, Liya Lugita (LPPM STIKES BHAKTI HUSADA BENGKULU, 2022)
Background : WHO noted that every year more than 300,000 women die from complications of pregnancy and childbirth. The main causes of maternal death are bleeding, gestational hypertension (preeclampsia and eclampsia) and sepsis. In Indonesia bleeding, hypertension in pregnancy and infection are still the most common causes of maternal death. The purpose of this study was to determine the relationship between obesity and the incidence of preeclampsia in pregnant women. Methods : This research is an analytical survey research design with a cross sectional approach. The population in this study were all pregnant women who visited the Manna City Health Center in July-November 2021 totaling 153 people. The sample of this study was 110 respondents who were taken at random systematically by dividing the desired number of samples using the Simple Random sampling method. Data were processed by univariate and bivariate analysisResults : from 110 respondents, there were 100 people (90.9%) who were obese and 10 people (9.1%) who were not obese and 97 people who did not have preeclampsia 97 people (88.2 %) and 13 people (11.8%) who had preeclampsia. From the statistical test results of the chi-square test, it is known that the calculated X2 value = 87.3 > X2 table = 5.991 with a value of = 0.000 (<0.05) meaning that there is a significant relationship between obesity and the incidence of preeclampsia in pregnancy at the Manna City Health Center.Conclusion : It is recommended for pregnant women to maintain a regular diet and exercise and regularly check their pregnancy to health workers.